2019
DOI: 10.1002/jbmr.3747
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Autosomal Dominant Hypocalcemia Type 1 With the Calcilytic NPSP795 (SHP635)

Abstract: Autosomal dominant hypocalcemia type 1 (ADH1) is a rare form of hypoparathyroidism caused by heterozygous, gain‐of‐function mutations of the calcium‐sensing receptor gene (CAR). Individuals are hypocalcemic with inappropriately low parathyroid hormone (PTH) secretion and relative hypercalciuria. Calcilytics are negative allosteric modulators of the extracellular calcium receptor (CaR) and therefore may have therapeutic benefits in ADH1. Five adults with ADH1 due to four distinct CAR mutations received escalati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 25 publications
(45 reference statements)
1
34
0
Order By: Relevance
“…Calcium-Sensing Receptor-Related Genetic Diseases and Therapeutic Interventions). Indeed, the NAM, NPSP795 (SHP635), has recently undergone clinical testing for its therapeutic potential in the treatment of ADH1 (Roberts et al, 2019).…”
Section: Ph Large Supraphysiological Changes In Buffer Ph Alter Thementioning
confidence: 99%
See 1 more Smart Citation
“…Calcium-Sensing Receptor-Related Genetic Diseases and Therapeutic Interventions). Indeed, the NAM, NPSP795 (SHP635), has recently undergone clinical testing for its therapeutic potential in the treatment of ADH1 (Roberts et al, 2019).…”
Section: Ph Large Supraphysiological Changes In Buffer Ph Alter Thementioning
confidence: 99%
“…NPS 2143 reduces the signaling responses of cells expressing gain-of-function ADH2-causing Ga 11 mutants (Babinsky et al, 2016;Gorvin et al, 2017;Roszko et al, 2017) NPS 2143 increases serum calcium and PTH concentrations in mouse models for ADH2 (Gorvin et al, 2017;Roszko et al, 2017) NAM, NPSP795, has been administered to five ADH1 patients in a phase IIa clinical trial and increased plasma PTH concentrations and reduced urinary calcium excretion (Table 3) (Roberts et al, 2019). However, circulating calcium concentrations were not altered in these patients, and the optimal dosing regimen of NPSP795 for ADH remains to be established.…”
Section: ) Adh2mentioning
confidence: 99%
“…(26) NPSP795 was shown to normalize increases in Ca 2+ i and pERK-signaling responses of cells stably expressing the Nuf mutant CaSR, which is in keeping with the reported effects of NPSP795 on ADH1-causing germline gain-of-function CaSR mutations. (23) Our in vivo studies showed that single-bolus administration of NPSP795 significantly increases plasma PTH concentrations in a dose-dependent manner in Nuf mice. However, substantially higher doses of NPSP795 were required to increase PTH secretion in Casr +/Nuf and Casr Nuf/Nuf mice compared with that required for WT mice ( Fig.…”
Section: Discussionmentioning
confidence: 73%
“…Consistent with this, NPSP795 has been previously shown to improve the gain-of-function caused by mutations located in the extracellular (Glu228Ala, Glu228Lys, and Gln245Arg) and transmembrane (Ala840Val) domains of the CaSR. (23) In conclusion, single-dose administration of NPSP795 has been shown to cause dose-dependent increases in PTH and to ameliorate the hypocalcemia in an ADH1 mouse model. Thus, the NPSP795 calcilytic represents a potential targeted therapy for ADH1.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation